Réponses

Meilleure réponse !
2014-07-17T19:23:12+02:00
1) développement
A = 2 ( 3x + 4 ) - 5 ( 1 - 2x )
   = 2 × 3x + 2 × 4 - ( 5 × 1 - 5 × 2x )
   = 6x + 8 - ( 5 - 10x )
   = 6x + 8 - 5 + 10x
   = 6x + 10x + 8 - 5
   = 16x + 3

B = 7 ( 2x - 3 ) + 12
   =  7 × 2x - 7 × 3 + 12
   = 14x - 21 +12
   = 14x - 9

2) résoudre l’équation   A = B
A = B ⇔  16x + 3 = 14x - 9
         ⇔   16x - 14x = -9 -3
         ⇔   (16 - 14)x = -9 + (-3)
         ⇔             2x = -12
         ⇔              x = -12 / 2
         ⇔              x = -6

EX 7 

1) on a    ( x + 3 ) / 2 =    ( 1 - 2x ) / 3
   donc    ( x + 3 ) × 3 =   2 × ( 1 - 2x )  le produit des extremes est egal au produit des moyens
2)   on a  ( x + 3 ) × 3 =   2 × ( 1 - 2x )
       ⇔    3x + 3 × 3  =  2 × 1 - 2 × 2x
       ⇔    3x +  9       =  2  -  4x     
       ⇔    3x +  4x       =  2  -  9   
       ⇔            7x       =  -7  
       ⇔              x       =  -7 / 7 
       ⇔              x       =  -1